The analysis of music composition learning of HL Music diploma program students in the international baccalaureate curriculum using Jean Piaget’s theory of cognitive development - Gunita Putri, Vinsensia; Mulyanto, Mulyanto; Widiastuti, Endang (Gelar: Jurnal Seni Budaya, 2024)
This study uses a qualitative case study method with three HL music students in the International Baccalaureate (IB) Diploma Programme. It aims to analyze the creative process of students who selected HL music out of interest but lacked prior musical theory or skills. The focus is on the Contemporary Music Maker HL Only assessment, where students produce a music composition. The composition process is analyzed using Jean Piaget's cognitive theory, particularly the stages of assimilation (integrating prior knowledge), accommodation (adapting to new knowledge), and equilibrium (balancing the two). The findings show that Piaget’s cognitive stages effectively guide students through the creative process. The quality of equilibrium each student achieves is reflected in their IB scores, demonstrating their ability to integrate and apply new knowledge. This study underscores the relevance of Piaget's cognitive theory as a foundation for developing creative skills in music education. It highlights the importance of understanding cognitive stages to support student learning in music composition. Further research is recommended to explore its application across different educational levels and cultural contexts.